Child Apologue: Mahmoud Darwish & the Palestinian Childhood - Khan, Shafaat Yar; Aslam, Muhammad; Khan, Nabiya (Journal of Research in Humanities, 2024)
This research explores Darwish’s thematic topography to understand how he inscribes the experiences of children throughout his poetic career. Basing this exploration on a corpus of 15 selections of his poetry (2000 pages long), this study traces all the verses about children in Darwish’s works. Data collection led to searching for the key words in the context of the relevant verses, followed by thematic mapping of the ideas and literary interpretations. In delimiting itself to children in Darwish’s poetry, this paper takes a different route from the previous research which consider Darwish “a propagandist for his country’s cause, a guerrilla fighting with pen and ink, rather than a serious poet whose prime subject-matter happens to be the tragedy of his country” (Johnson-Davies viii-ix). But the theoretical stance of this paper is that “childhood is constructed by social forces, political interests, cultural phenomena, and macro-societal and political changes” (Diana 4-5), “it participates in the processes of generating meaning and institutional practices” (Nashef 160). The findings of the research establish that children were a lifelong concern with Darwish who highlighted the implications of armed conflict for the Palestinian children. It shows his increasing pessimism regarding the possibilities of a national structure of the Palestinian nation if Palestinian children are deprived of peaceful life. The findings have relevance to the present afflictions committed against Palestinian children in the Israel- Gaza war and their effects on the budding generation of Palestinians.